Exploring the need for a clinical decision support system for deprescribing - A qualitative interview study - Aryoutha Asmar Talani; Tora Hammar; Ylva Böttiger (Exploratory Research in Clinical and Social Pharmacy)
Background: Deprescribing (i.e., the process of discontinuing an inappropriate medication) requires time, knowledge, and care, but there is a lack of education, support, and guidelines for this important clinical task. A clinical decision support system (CDSS) aims to influence the quality of care by combining structured medical knowledge with patient-specific information to generate recommendations. Objective: The objective was to examine the need to develop a CDSS for drug deprescribing. Furthermore, this study aimed to examine the obstacles to deprescribing and potential users' requirements for a CDSS for deprescribing. Methods: The qualitative design consisted of semistructured interviews with physicians (n = 10) in Sweden from different disciplines, including geriatrics, primary care and internal medicine. The interviews were conducted using a predefined guide containing multiple questions about any challenges related to deprescribing and the perceived need for a CDSS. A qualitative content analysis was performed to analyse the empirical data. Results: The interviews provided several aspects of the difficulty of deprescribing medicines. The structure and usability of the CDSS knowledge database in clinical practice needs to be ensured from the outset. Physicians needs fast, simple and up-to-date information filtered, summarized and synthesized from reliable sources. The information should preferably be integrated into pre-existing electronic health record. Conclusion: There is a need to develop a CDSS for deprescribing. There is little, if any, guidelines or support for deprescribing, which is regarded as a large obstacle. The current findings contribute to further knowledge regarding the perspective of physicians when deprescribing medication.